Evaluation of Prescription Pattern of Analgesic use Among Ambulatory elderly in Southwestern Nigeria. (2020)
Background: Inappropriate prescribing of analgesics has a global impact on the health of elderly patients and the society. Empirical evidence on the prescription of analgesics among elderly Nigerians is scarce. Objectives: The objective of the study was to evaluate the prescription pattern of analgesics and describe the co-prescribing of gastroprotective agents with non-steroidal anti-inflammatory drugs (NSAIDs) among elderly patients at the geriatric center, University College Hospital, Ibadan. Methods: A retrospective cross-sectional, hospital-based study was carried out among elderly patients(≥60 years) who were prescribed analgesics. Using a data extraction sheet, information on demographic characteristics, drug utilization pattern, and morbidities was obtained from patients’ case files via electronic health records. Results: A total of 337 patients case files were reviewed, the mean age was 72 ± 8.8 years, and 210 (62.3%) were females. There were a total of 2074 medications prescribed, with 733 (35.3%) being analgesics. Majority of the elderly patients(259, 76.9%) were on nonopioids, with 252 (74.8%) on NSAIDs. Paracetamol was the most commonly prescribed analgesics (181, 24.6%), followed by diclofenac/misoprostol (177, 24.1%), opioid analgesic prescribed was 88 (12.0%), with paracetamol/codeine 58 (65.9%), and tramadol 16 (18.2%) being the most prescribed opioid. A significant proportion of the hypertensive elderly patients (160, 78.8%; P < 0.036) were on NSAIDs. The oral route of administration (302, 89.6%) was the most common route of administration. Majority (310, 92%) of elderly patients taking NSAIDs had a co-prescription for gastroprotective agents. Conclusions: Majority of hypertensive patients were on NSAIDs. This calls for prompt awareness of rational analgesic use among the elderly to improve management and their survival